2019
DOI: 10.1177/2055116919849979
|View full text |Cite
|
Sign up to set email alerts
|

Colonic malignant peripheral nerve sheath tumour in a cat

Abstract: Case summary A 14-year-old male neutered domestic mediumhair cat presented with a 4 month history of inappetence and weight loss. Pertinent abnormalities on haematology and biochemistry included a mild microcytic regenerative anaemia (packed cell volume [PCV] 24% [reference interval (RI) 30–45%], mean cell volume 30.8 fl [RI 40–45 fl], absolute reticulocyte count 326.8 × 10 12 ) and increased alkaline phosphatase activity (76 IU/l; RI <50 IU/l). Abdominal ultrasound and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Apart from the above-mentioned tumors, TK expression and/or TKI treatment has been investigated in feline pulmonary carcinomas [146,147], endometrial adenocarcinoma [46], feline histiocytic disorders [54], renal cell carcinoma [58,59,148,149], iris melanomas [150], granulosa cell tumors [56], adrenal cortex carcinoma [56], thyroid gland carcinoma [56], Non-Hodgkin's lymphoma [56], leiomyosarcoma of the gastrointestinal tract [140,151,152], osteosarcoma [57], oligodendrogliomas and subependymomas [153], colonic malignant peripheral nerve sheath tumors [154], gemistocytic astrocytoma [155], Merkel cell carcinoma [156], pancreatic adenocarcinoma [157,158], chemodectoma [159], tracheal adenocarcinoma [160] and hypereosinophilic syndrome [161].…”
Section: Other Malignanciesmentioning
confidence: 99%
“…Apart from the above-mentioned tumors, TK expression and/or TKI treatment has been investigated in feline pulmonary carcinomas [146,147], endometrial adenocarcinoma [46], feline histiocytic disorders [54], renal cell carcinoma [58,59,148,149], iris melanomas [150], granulosa cell tumors [56], adrenal cortex carcinoma [56], thyroid gland carcinoma [56], Non-Hodgkin's lymphoma [56], leiomyosarcoma of the gastrointestinal tract [140,151,152], osteosarcoma [57], oligodendrogliomas and subependymomas [153], colonic malignant peripheral nerve sheath tumors [154], gemistocytic astrocytoma [155], Merkel cell carcinoma [156], pancreatic adenocarcinoma [157,158], chemodectoma [159], tracheal adenocarcinoma [160] and hypereosinophilic syndrome [161].…”
Section: Other Malignanciesmentioning
confidence: 99%
“…Gastrointestinal MPNSTs are rarely reported in cats, and only two cases have been reported to our knowledge [ 2 , 18 ]. Ribas et al reported a small intestinal MPNST without metastasis in a 5-year-old female spayed chinchilla cat that was treated with complete surgical excision.…”
mentioning
confidence: 99%
“…Boland et al described a colonic MPNST with hepatic metastasis in a 14-year-old male neutered domestic medium-hair cat that was treated with surgical resection and metronomic cyclophosphamide. The cat experienced recurrence, and post-mortem examination identified MPNST within the kidneys and liver 18 months postoperatively [ 2 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations